(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article presents the results of the research of the indicators of the competitive activity of highly qualified female teams in beach handball at the final stage of attacking actions with the use of "specialist-player" and "player-player" interactions. The purpose of the study is to determine the indicators of the implementation of tactical actions at the final stage of the attack of highly qualified female teams in beach handball. Objectives of the study. To determine the quantitative indicators of the attacking actions of highly skilled female beach handball teams using different methods of interaction at the final stage of the attack. To analyze the quantitative and qualitative indicators of the use of different technical techniques at the end of attacking actions with different ways of interactions at the final stage of the attack in highly qualified female beach handball teams. Research results. It has been established that highly skilled female beach handball teams use two types of interactions — "specialist-player" and "player-player" in the final stage of attacking actions, when they are completed by field players. According to the results of the observation, it was found that the use of throws after pirouettes, their greater effectiveness and efficiency get significantly higher rates. Conclusions. According to the results of the observation, it was established that the players of highly qualified female beach handball teams use "specialist-player" and "player-player" interactions at the final stage of attacking actions. At the same time, the number of "player-player" interactions is significantly higher (p<0.001). The efficiency indicators of these interactions do not differ among themselves. At the end of attacking actions, highly qualified female beach handball teams prefer throws after pirouettes, throws in flight and direct throws. Significantly higher indicators of application, their effectiveness and efficiency were established in throws after pirouettes and significantly lower direct throws.